Pro JavaScript development : coding, capabilities, and tooling - Odell, Den (Expert's voice in Web development., 2014)
Pro JavaScript Development is a practical guide for front-end web developers who are experienced at building web pages with HTML, CSS, and JavaScript, and now wish to advance their JavaScript skills to a higher level. You will learn how to build large, well-structured, high quality, mobile-optimized web sites and apps, using the latest supported browser APIs, language features, and tools. This book teaches and shows you in practical hands-on terms how you can: Master the performance, reliability, stability, and code manageability of your JavaScript Understand and use efficient object-oriented code, including full understanding of the 'this' keyword Architect effective testing and error handling, including linting, TDD, BDD, and automation Managing code dependencies with AMD and RequireJS Develop for mobile, build games, and set up real-time communication using recent APIs such as WebRTC Effectively use frameworks such as Knockout.js, Backbone.js, and AngularJS to enhance your apps Code using JavaScript language abstractions such as CoffeeScript, Dart, and TypeScript Manage the back-end with Node.js, and build tools such as Grunt Using real-world applications that you'll build yourself, Pro JavaScript Development has unique, practical content that will make you a better JavaScript developer. Become a master of the latest JavaScript coding techniques and tools, and harness its best capabilities today.